2020
DOI: 10.15252/embj.2020105496
|View full text |Cite
|
Sign up to set email alerts
|

Translational adaptation to heat stress is mediated by RNA 5‐methylcytosine in Caenorhabditis elegans

Abstract: Methylation of carbon-5 of cytosines (m 5 C) is a post-transcriptional nucleotide modification of RNA found in all kingdoms of life. While individual m 5 C-methyltransferases have been studied, the impact of the global cytosine-5 methylome on development, homeostasis and stress remains unknown. Here, using Caenorhabditis elegans, we generated the first organism devoid of m 5 C in RNA, demonstrating that this modification is non-essential. Using this genetic tool, we determine the localisation and enzymatic spe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 98 publications
1
25
0
Order By: Relevance
“…mter-4(syb3662) results in an K262E and R263E substitution in MTER-4. nsun-4(mj457) results in a C390A catalytic dead conversion in NSUN-4 and was reported previously ( Navarro et al, 2021 ). All mutants were crossed with SJ4100— zcIs13[hsp-6::GFP]— to generate hsp-6 reporter strains.…”
Section: Methodssupporting
confidence: 85%
See 1 more Smart Citation
“…mter-4(syb3662) results in an K262E and R263E substitution in MTER-4. nsun-4(mj457) results in a C390A catalytic dead conversion in NSUN-4 and was reported previously ( Navarro et al, 2021 ). All mutants were crossed with SJ4100— zcIs13[hsp-6::GFP]— to generate hsp-6 reporter strains.…”
Section: Methodssupporting
confidence: 85%
“…GTPBP7, MTERF4, and NSUN4 are highly conserved and their counterparts in Caenorhabditis elegans are MTG-1 (33% identical), MTER-4 (21%), and NSUN-4 (34%), respectively. In C. elegans , the methyltransferase activity of NSUN4 for mitochondrial protein synthesis was shown to be dispensable ( Navarro et al, 2021 ), suggesting that its importance may instead lie in its interaction with the conserved core of the mtLSU. To test the importance of complex formation of the three protein factors with the mtLSU during assembly in vivo, we used C. elegans as a model organism and introduced mutations at locations in the three factors that we predicted would disrupt binding to the mtLSU without affecting expression, mitochondrial targeting or protein folding ( Figure 3A , Figure 3—figure supplement 1 , Figure 3—figure supplement 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of transfer (t)RNA methylation in C. elegans indicated that 5-methyl cytosine (m5C) loss leads to reduced translation efficiency of UUG-rich transcripts and impaired fertility, suggesting a role for m5C tRNA methylation in translational adaptation to higher temperatures or heat stress [ 73 ]. Another recent study of ribosomal (r)RNA in C. elegans indicated that the loss of a single enzyme, NOL1/NOP2/Sun Domain Family, Member 1 (NSUN-1), which is required for rRNA methylation, has highly specific effects on the organism’s development and physiology [ 74 ].…”
Section: Rna Methylation In Caenorhabditis Elegansmentioning
confidence: 99%
“…However, many studies have found that aberrant m5C modification may lead to a variety of abnormal conditions such as stress disorder, mitochondrial dysfunction, embryogenesis and neurodevelopmental abnormalities, and even tumor cell proliferation, migration, and tumorigenesis, etc. (Navarro et al, 2021;Walworth et al, 2021). Research in recent decades has found that multiple m5C methyltransferases are associated with some cancer phenotypes.…”
Section: Rna 5-methylcytosine Epigenetic Modification In Hepatocellular Carcinomamentioning
confidence: 99%